La falencia del modelo de neutralidad Catarí en la crisis de Medio Oriente - Banda Hallo, Carlos Andrés (2018)
Neutrality is the quality with which a State has to remain oblivious to any conflict. The capacity to maintain it will depend on the State that practices it, the importance of staying attached to the factors described methodologically will determine its effectiveness and effectiveness. Without fulfilling that will grant the right and qualities of a neutral State. The bipolarity that exists in the Middle East limits the actors to only contemplate which side they can join and which to reject. Without a doubt, it is interests that dictate the way forward for the hegemonic states, in this case Saudi Arabia and Iran, and in the same way limit the functioning and development of small nations that do not have enough force military to deal with conflicts. The purpose of this research is to analyze the effectiveness of Qatar´s neutrality, through indicators obtained after the study of authors and academics who have described and pointed out essential characteristics that neutrality must fulfill when exercised.